KNOWLEDGE, ATTITUDE AND PRACTICE (KAP) TOWARDS BLOOD DONATION AMONG E-PJJ DEGREE NURSING STUDENTS - Rosuzeita Fauzi; Nur Salma Jamaludin; Noor Fathiah Ahmed; Siti Khuzaimah Ahmad Sharoni (The Malaysian Journal of Nursing (MJN), 2022)
Background: The shortage of blood in any hospital in every state is due to an increase in blood demand for severe critical injuries, with a fewer voluntary and limited number of replacement blood donors. The case is worst when there is a lack of voluntary blood donors. Objective: This study aims to assess the knowledge, attitude, and practice (KAP) towards blood donation among e-PJJ degree nursing students. Methods: A cross-sectional survey was conducted among 109 e-PJJ degree nursing students at UiTM Puncak Alam campus. Students who participated using purposive sampling (n=109) were asked to complete a set of self-administered questionnaires. Knowledge, attitude, and practice questionnaire were used to measure KAP towards blood donation. The association between knowledge and attitude was determined using Pearson correlation. Results: The mean (SD) score for the level of knowledge towards blood donation is 15.59 (4.59) and for the attitude is 5.17 (1.03). Percentage of practice, 65 (59.6%) of the students said that they donate blood voluntarily, and just over half of the students, 103 (94.5%), reported that they are willing to become a regular donor. The level of knowledge has a significant positive correlation with the attitude towards blood donation (r=1.00, p< 0.01). Conclusion: In general, most students in this study had good knowledge and a positive attitude towards blood donation. However, blood donation was still an unsatisfactory practise. A targeted approach to improving blood donation knowledge in this population should be implemented as one of the approaches to improve blood donation rates in the future.